Synergistic effect of pyridate-based herbicide mixtures for controlling multiple herbicide-resistant kochia (Bassia scoparia) - Sachin Dhanda; Vipan Kumar; Patrick W. Geier; Randall S. Currie; J. Anita Dille; Augustine Obour; Elizabeth A. Yeager; Johnathan Holman (Weed Technology)
Multiple herbicide classes–resistant (MHCR) kochia poses a serious concern for producers in the Central Great Plains, including western Kansas. Greenhouse and field experiments were conducted at Kansas State University Research and Extension Centers near Hays and Garden City, KS, to evaluate pyridate-based postemergence herbicide mixtures for controlling MHCR kochia. One previously confirmed MHCR population (resistant to atrazine, glyphosate, dicamba, and fluroxypyr) and a susceptible (SUS) kochia population were tested in a greenhouse study. The kochia population at Hays field site was resistant to atrazine, dicamba, and glyphosate, whereas the kochia population at the Garden City site was resistant to atrazine and glyphosate. Colby’s analysis revealed synergistic interactions when pyridate was mixed with atrazine, dicamba, dichlorprop-p, fluroxypyr, glyphosate, or halauxifen/fluroxypyr and resulted in ≥94% control and shoot dry-biomass reduction of MHCR kochia in a greenhouse study. Similarly, synergistic interactions were observed for MHCR kochia control in fallow field studies at both sites when pyridate was mixed with glyphosate or atrazine. Kochia control was increased from 26% to 90% with the application of glyphosate + pyridate and from 28% to 95% with atrazine + pyridate at both sites as compared to separate applications of glyphosate or atrazine. This is the first report for such a strong synergistic effect for both glyphosate and atrazine mixtures with pyridate on a weed resistant to both. All other pyridate-based herbicide mixtures showed an additive interaction and resulted in better control of MHCR kochia (87% to 100%) as compared to their individual applications (23% to 92%) across both sites except 2,4-D. These results suggest that pyridate can play a crucial role in various postemergence herbicide mixtures for effective control of MHCR kochia.